Woven Tunics found in Shetland (Proceedings of the Society of Antiquaries of Scotland, 1852)
Dr. John Alexander Smith communicated an account of a discovery of two woven tunics alongside two skeletons, all of which had been buried in a bog on top of a hill called Nosewick, on the mainland of Shetland. Dr. Bell who had been present at the discovery exhibited the tunics and presented them to the Society. Some of the bones which had been wrapped in the tunics were stained a deep brown by the moss, which seemed to have preserved them. It was resolved at the meeting that portions of the tunic would be sent off to Herr Rafn of Copenhagen to compare it with discoveries made in Denmark.